Kearifan Abdurrahman Wahid (Gus Dur) Terhadap Budaya Lokal Indonesia Ucapan “Assalamualaikum” - moh mustaqim (Pena Islam Jurnal Pendidikan Agama Islam, 2019)
He has taken the time to think about Islamic values, nationality, local culture, and play an important role in the development of Islam, the Indonesian nation. He maintains religious traditions, ethnicity, including cross-groups, and politics. Gus Dur is a thinker who often gets about from other people. One of his remarks as the implementation of the idea of ​​"indigenous Indigenous Islam" which once contained controversy, namely "Assalamu'alaikum" which was equated by Gus Dur with "Ahlan wa Sahlan and the idea of" Pribumi Islam "made a commotion among the NU itself. According to him Islam does not come into conflict with culture, but both of them enrich each other, even though there are differences. Islam is peaceful and anti-violence, therefore Muslims need not act violently in defending Islam with any action, let alone in the name of Islam.. Islam itself is anti-violence, Islam is peaceful and secure. Islam should protect people who are weak and protect from arbitrary acts outside the law that are often carried out by organizations that act arbitrarily and willingly. Islam sided with the oppressed minority. According to him the relationship between Islam and the State with two offers, namely making Islam as a social ethic in the life of the state and the introduction of Islam. Abdurrahman saw the Indonesian nation at that time there was a product of the intense struggle of primary concern: revitalizing the traditional Islamic treasures, gait of modernity, and seeking answers to concrete problems that were addressed by Muslims in Indonesia.